ANALISIS KUALITAS LAYANAN APLIKASI BELI.IN MENGGUNAKAN METODE PIECES FRAMEWORK - Hadiputra, Karel Enrico; Zaman, Baizul; Bahri, Syamsul (KHARISMA Tech, 2024)
Beli.in is an android-based deposit service provider application that focuses on Makassar City, but the quality of service in the Beli.in application has never been analyzed. To find out the quality of service on the Beli.in application, therefore this study aims to analyze the quality of service of the Beli.in application using the PIECES method. This research uses the PIECES method because this method can focus on solutions to problems that have been identified in terms of matters related to Performance, Information, Economy, Control and security, Efficiency, and Service. Analysis of the Beli.in application using the PIECES method in this study is carried out by collecting answers from respondents who have answered the questionnaire, then the results of the answers from these respondents will be calculated so that the quality of service in the Beli.in application can be analyzed. Respondents will answer several questions that will be provided via Google Form.